Buy Now: How Amazon Branded Convenience and Normalized Monopoly - Emily West (The MIT Press, 2022)
How Amazon combined branding and relationship marketing with massive distribution infrastructure to become the ultimate service brand in the digital economy. Amazon is ubiquitous in our daily lives—we stream movies and television on Amazon Prime Video, converse with Alexa, receive messages on our smartphone about the progress of our latest orders. In Buy Now, Emily West examines Amazon's consumer-facing services to investigate how Amazon as a brand grew so quickly and inserted itself into so many aspects of our lives even as it faded into the background, becoming a sort of infrastructure that can be taken for granted. Amazon promotes the comfort and care of its customers (but not its workers) to become the ultimate service brand in the digital economy. West shows how Amazon has cultivated personalized, intimate relationships with consumers that normalize its outsized influence on our selves and our communities. She describes the brand's focus on speedy and seamless ecommerce delivery, represented in the materiality of the branded brown box; the positioning of its book retailing, media streaming, and smart speakers as services rather than sales; and the brand's image control strategies. West considers why pushback against Amazon's ubiquity and market power has come mainly from among Amazon's workers rather than its customers or competitors, arguing that Amazon's brand logic fragments consumers as a political bloc. West's innovative account, the first to examine Amazon from a critical media studies perspective, offers a cautionary cultural study of bigness in today's economy.
Keywords: 650; History of specific companies / corporate history; Web-marketing; Media studies